2020
DOI: 10.1002/num.22621
|View full text |Cite
|
Sign up to set email alerts
|

On solutions of time‐fractional advection–diffusion equation

Abstract: In this paper, we present an attractive reliable numerical approach to find an approximate solution of the time‐fractional advection–diffusion equation (FADE) under the Atangana–Baleanu derivative in Caputo sense (ABC) with Mittag–Leffler kernel. The analytic and approximate solutions of FADE have been determined by using reproducing kernel Hilbert space method (RKHSM). The most valuable advantage of the RKHSM is its ease of use and its quick calculation to obtain the numerical solution of the FADE. Our main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…First, we express some RKHSs mostly needed through this study and can be found in many papers (see, e.g. [13,14]). Then we derive the expression of the reproducing kernel function (RKF) for each defined RKHS.…”
Section: On Reproducing Kernel Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…First, we express some RKHSs mostly needed through this study and can be found in many papers (see, e.g. [13,14]). Then we derive the expression of the reproducing kernel function (RKF) for each defined RKHS.…”
Section: On Reproducing Kernel Theorymentioning
confidence: 99%
“…Here, we don't present the expression of the reproducing kernel function Z x m ( ) of the space 3 because it is so long. The interested reader is referred to[14] for more details about this point.2Theorem 2.11. We obtain the RK function R t h ( ) of the space…”
mentioning
confidence: 99%
“…The Riccati differential equation is employed across diverse disciplines like physics, engineering, biology, control theory, signal processing, and finance [25], [6], [20]. The fractional Riccati equation holds significance in numerous physics and engineering contexts [36], [33], [43], [40], [8], [11], [23], [35], [45]. Many investigators have examined the numerical solution of this problem [24], [22], [21], [30], [42], [5], [7].More convenientreferences for this equation can be found in [18], [37], [1], [30], [38], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Akgül and Modanli [36] proposed the Crank-Nicholson difference scheme method for the third order fractional partial differential equation with ABFD. Attia et al [37] developed the computational approach to find an approximate solution of the TFADE.…”
Section: Introductionmentioning
confidence: 99%